An Error Analysis on the Use of Simple Past Tense in Students’ Recount Text Writing - Griffit Patricia Lionny; Hermariyanti Kusumadewi (JEdu: Journal of English Education, 2022)
This research was conducted based on the phenomenon happened in the school. The students had low ability in grammar. They got difficulty in constructing sentences by using some tenses. Therefore, this thesis discussed the error analysis on using simple past tense in writing recount text. The purpose of this research was to classify the types of errors made by the students and find out the sources of errors which students made on using past tense in writing recount text. This research was conducted based on descriptive qualitative analysis. The subjects of the research were the students at the first semester of SMA Mardi Yuana Depok Class X Social III which consisted of 20 students, it was considered by using purposive sampling technique. In collecting the data, this research used writing task to identify the students‟ errors on using action verb in writing recount text based on linguistic category taxonomy and sources of errors according to Brown’s theory. The result of the research showed that there were 4 types of errors made by the students. The highest two common errors were Misinformation errors 30 or 37,5% and Omission errors 24 or 30 %. The lowest two errors were Addition errors that were 14 items or 17,5% and Mis-ordering with 12 items or 15%. Based on the total result types of errors, this research found that Interlingual Transfer was the major source of errors made by the students.